The role of dulaglutide in the treatment of alcohol use disorder: a case report - Olivia Hill; Sarah Hughes; Aakanksha Singh; Michael Ang-Rabanes; Raja Mogallapu (Frontiers in Psychiatry)
Glucagon-like peptide 1 (GLP-1) receptor agonists, medications commonly employed in the treatment of type 2 diabetes mellitus, have illustrated several additional benefits, including weight loss and potentially reduce addictive cravings. Several studies have indicated that GLP-1 receptor agonists may be effective in treating Alcohol Use Disorder (AUD), for which current pharmacologic therapies are often inadequate. Proposed mechanisms include modulation of dopaminergic transmission and reduced gastric emptying, both of which reduce alcohol craving and tolerance. This case report discusses dulaglutide’s ability to reduce alcohol consumption. During a visit to an outpatient behavioral health clinic, a 44-year-old male was evaluated for weight loss. His medical history revealed a BMI of 41.8, hypertension, major depressive disorder, and pre-diabetes. The individual also reported the consumption of approximately ninety beers per month and was in the pre-contemplation phase of change. As part of the treatment plan, the patient was prescribed dulaglutide to manage pre-diabetes and facilitate weight loss. During subsequent appointments, the individual not only experienced weight loss but also noted a substantial reduction in alcohol cravings and consumption. However, following a lapse in insurance coverage the following year, the individual had to discontinue his dulaglutide, resulting in a return to previous drinking patterns. Future research should focus on confirming existing animal study results in humans, with the hope that GLP-1 receptor agonists can become a mainstay treatment for AUD.